Incidence of acute kidney injury and assessment of its associated risk factors in patients undergoing transarterial chemoembolisation for hepatocellular carcinoma - Saeed, Kamran Muddasar; Afifa Aftab; Muhammad Abu Bakar; Junaid Iqbal (Journal of the Pakistan Medical Association, 2022)
Objectives: To determine the incidence of acute kidney injury in intermediate stage hepatocellular carcinoma patients undergoing trans-arterial chemoembolisation, and to analyse various causative factors. Method: The retrospective study was conducted at the Shaukat Khanum Cancer Memorial Hospital, Lahore, Pakistan, and comprised data from January 2012 to December 2015 of adult patients of either gender with intermediate stage hepatocellular carcinoma and undergoing trans-arterial chemoembolisation with Child-Pugh score A. Outcomes were measured in the form of development of acute kidney injury, and its causative factors. Data was analysed using SPSS 20. Results: Of the 133 patients, 90(67.6%) were male. The overall mean age of the sample was 59±8.4 years (range: 26-86 years). Of these, 19(14%) developed acute kidney injury. Higher alpha-fetoprotein levels and lower albumin levels were found to be the significant causative factors (p<0.05). Conclusion: The incidence of trans-arterial chemoembolisation-related acute kidney injury was 14%. Higher baseline alpha-fetoprotein and lower baseline albumin levels were found to be the significant risk factors. Key Words: Transarterial chemoembolisation, TACE, Acute Kidney Injury, AKI, Hepatocellular carcinoma, HCC, Risk factors.